Cryptographic Strain‐Dependent Light Pattern Generators (Adv. Mater. Technol. 1/2022). Issue 1 (7th January 2022) - D'Elia, Francesca; Pisani, Francesco; Tredicucci, Alessandro; Pisignano, Dario; Camposeo, Andrea
Abstract : Cryptographic Magic Windows In article number 2101129, Francesco Pisani, Andrea Camposeo, and colleagues introduce stretchable and 3D printed cryptographic magic windows capable of generating complex patterns, including micro‐QR‐codes, by refraction of light in the visible range. The information carried by a light pattern, that is encrypted in the 3D topography of the magic windows, is unveiled by projection of the light pattern on a screen.